Apert Syndrome - Nengah Suparta; Hartono Hartono; Sunartini Sunartini (Indonesian Pediatric Society, 1991)
A case of Apert syndrome in a male child of 5 months old hos been reported. The diagnosis was based on the clinical appearance (phenotype) showing acrocephaly and syndactily of both hands and feet, supported by skull rontgenography and ultrasonography.The patient was the third child from normal parents, and the two other children were normal. Apert syndrome is a genetic dominant automal disease; and because there were no other sufferer from the family history, the occurrence of this syndrome has been caused by a new mutation. Symptomatic therapy such as the administration of acetazolamide for hydrocephalus and vitamin suplement to improve his general condition and even physical physiotherapy have been carried out. Genetic counselling to the couple has been provided as well.